2023
DOI: 10.1039/d3dt01042b
|View full text |Cite|
|
Sign up to set email alerts
|

Catalytic exploration of NHC–Ag(i)HMDS complexes for the hydroboration and hydrosilylation of carbonyl compounds

Claudia P. Giarrusso,
Daniel V. Zeil,
Victoria L. Blair

Abstract: The synthesis and full characterisation of two silver(I) amido complexes, stabilised by ancillary N-heterocyclic carbene (NHC) ligands is presented. The light stable complexes [Ag(IDipp)HMDS] 3 and [Ag(IAd)HMDS] 4 were explored...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…It is worth mentioning that, compared to Ag-based CMAs, the applications of Cu-based CMA complexes in the hydrosilylation of carbonyl compounds are rare in the literature, and, therefore, these results showcase the potential of more sustainable systems for the synthesis industrially interesting silyl ethers. 26,31,33 On the other hand, complex 2a was inactive under these reaction conditions, underlining the necessity of the 1 H -benzotriazolyl anion in the complex scaffold (Table 2, entry 12). A wide range of aldehydes and ketones were then tested, using mainly catalysts 5a and 6a (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth mentioning that, compared to Ag-based CMAs, the applications of Cu-based CMA complexes in the hydrosilylation of carbonyl compounds are rare in the literature, and, therefore, these results showcase the potential of more sustainable systems for the synthesis industrially interesting silyl ethers. 26,31,33 On the other hand, complex 2a was inactive under these reaction conditions, underlining the necessity of the 1 H -benzotriazolyl anion in the complex scaffold (Table 2, entry 12). A wide range of aldehydes and ketones were then tested, using mainly catalysts 5a and 6a (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, all the experiments were set up and performed outside of a glovebox, as the CMA catalysts are air and moisture stable, in contrast to other literature works using catalysts that require special handling. 26,31,33 Solvent screening revealed that DCE was the most suitable choice for this reaction (entries 2–4). Moreover, time control experiments showed that only 1 hour, instead of 16, is long enough to achieve the formation of the cyclized product 8a in excellent yields (entry 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the C NHC signal in 3-Ag appears as a doublet of doublets at 190.59 ppm ( 1 J Ag−C = 145.4 and 167.0 Hz for 107 Ag and 109 Ag, respectively, see Figure 4f), in agreement with the literature. 93,103 The neopentylidene signal in 3-Ag is observed as a broad doublet, displaying a coupling constant of 30.3 Hz with silver (Figure 4f). These observations confirm the interaction of silver with the NHC and both neopentylidene moieties in 3-Ag on the NMR time scale.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…There are different reasons, either because it blocks a coordination of an additional ligand, because it leaves the perfect cavity in the first coordination sphere around the metal to interact with the substrates, and actually, it is common then that the most sterically protected metal centre is the most effective catalytically. 237,238…”
Section: Fields Of Practical Utility Of %Vbur and Steric Mapsmentioning
confidence: 99%